Fungsi Program Pembinaan Keagamaan Bagi Narapidana Di Lembaga Pemasyarakatan - Fathur Rohman AR (Pena Islam Jurnal Pendidikan Agama Islam, 2020)
Religious development in correctional institutions is important, because the religious value here is to function to organize the life of an inmate to become a person of good behavior. The purpose of this study was to determine the strategy of Islamic religious guidance in Class IIB Penitentiary in Mojokerto and the vision, mission, goals, objectives, policies, programs and activities of Islamic religious guidance in Class IIB Penitentiary in Mojokerto. Based on the results of research conducted by researchers it can be seen that the Mojokerto IIB Class Correctional Institution in carrying out one of its duties is providing coaching to implement strategies in collaboration with LDNU Mojokerto Regency and several other religious institutions such as the Ministry of Religious Affairs and Islamic Boarding School Az-Zahroh as coaches who are experts in the field of Islam. The policies implemented in relation to Islamic religious guidance in Class IIB of Mojokerto include the provision of remissions or deductions from prison terms for those who are well-versed in religious activities. The program and activities of Islamic religious guidance carried out in Class IIB Mojokerto Prison include: 1) Habit of five-time prayer discipline, 2) Study of routine books, 3) Reading Al-Qur'an, 4) Istighosah.